2018
DOI: 10.1039/c8py00939b
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatically degradable star polypeptides with tunable UCST transitions in solution and within layer-by-layer films

Abstract: Enzymatically degradable star polypeptides exhibit robust UCST-type transitions in aqueous solution and within layer-by-layer assembled films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…previously, the UCST of this enzymatically degradable star polymer is tunable through degree of ureido modification and by change length of polypeptide arms [51]. Ureido groups containing polymer i.e.…”
Section: Figure 12mentioning
confidence: 99%
See 1 more Smart Citation
“…previously, the UCST of this enzymatically degradable star polymer is tunable through degree of ureido modification and by change length of polypeptide arms [51]. Ureido groups containing polymer i.e.…”
Section: Figure 12mentioning
confidence: 99%
“…Synthesis scheme for dendritic SPOC polymers using G4-PAMAM dendrimer as initiator (core) and protected NCA as monomer via ROP (KOCN -potassium cyanate). Reproduced with permission from [51], Copyright © 2018, The Royal Society of Chemistry.…”
Section: Figure 12mentioning
confidence: 99%
“…One might speculate as well that the sterically restricted geometry of the star polymer hampers the formation of intermolecular hydrogen bonds, which are crucial for the UCST-type response. However, Zhou et al demonstrate that in the case of star-shaped polypeptides (star-poly(ʟ-ornithin- co -ʟ-citrullin) (SPOC), the increase in arm length from ≈60 kDa to ≈100 kDa results in an increase in the UCST-type phase transition temperature from 18 °C to 31 °C [ 314 ] ( Figure 9 , part C). Although analogous to the star-shaped P(PAAm- co -AN) of Qi et al, the UCST behavior is based on hydrogen bonding, the steric confinement of the polypeptide chains does not seem to hamper attractive intermolecular interactions in this case [ 313 ].…”
Section: Reviewmentioning
confidence: 99%
“…Although analogous to the star-shaped P(PAAm- co -AN) of Qi et al, the UCST behavior is based on hydrogen bonding, the steric confinement of the polypeptide chains does not seem to hamper attractive intermolecular interactions in this case [ 313 ]. Moreover, it is demonstrated that the high local concentration of functional groups and therefore strong polymer–polymer interactions lead to a higher T c of the star polypeptide compared to a linear analogue with matching polymer chain length and similar composition [ 314 ]. Interestingly, the dendritic topology of the star polypeptide revealed a very low concentration dependency of the phase transition temperature.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation